Clustering of Eligibility and Characteristics of Smart Indonesia Card Recipients for College using Agglomerative Hierarchical Clustering - Ryando, M. Bucci; Sutarman, Sutarman (JURNAL SISFOTEK GLOBAL, 2024)
Since 2023, the Smart Indonesia Card or Kartu Indonesia Pintar-Kuliah (KIP-K) has two schemes. Consisting of KIP-K Scheme 1, where scholarship recipients are exempted from tuition fees and receive living allowances during the KIP-K scholarship period and KIP-K Scheme 2, where scholarship recipients are only exempted from tuition fees without receiving living allowances. Lack of information about the characteristics of prospective KIP-K scholarship recipients is a problem in itself. Many universities/institutions are not on target in providing this scholarship. This study aims to obtain clusters of recipients of KIP-K Scheme 1, KIP-K Scheme 2, and Not Eligible who are received and to obtain the characteristics of recipients of KIP-K Scheme 1, KIP-K Scheme 2, and Not Eligible who are received. This research method uses the CRISP-DM (Cross-Industry Standard Process for Data Mining) approach consisting of the stages of Business Understanding, Data Understanding, Data Preparation, Modeling, Evaluation, and Deployment and uses a combined method of Agglomerative Hierarchical Clustering with Average Linkage and uses the Calinski-Harabasz Index to test the validity of the cluster. The results of the study showed that the best cluster to explore was in 10 clusters with a Calinski-Harabasz Index value of 34.88236681148884. It was concluded that the feasibility of Scheme 1 KIP-K in cluster 8, 9 and 10.